PUBLIC PRIVATE PARTNERSHIP DALAM PROGRAM PENINGKATAN KOMPETENSI TENAGA KERJA DAN PRODUKTIVITAS (PKTKP) BERBASIS PEMAGANGAN DALAM NEGERI DI PROVINSI LAMPUNG - Rahayu Sulistiowati; Ita Prihantika; Asmiati (GoAcademica Research dan Publishing, 2022)
The domestic apprenticeship program in Lampung Province still encounters problems, such as the socialization process that is carried out less than optimally so that only a few companies are interested in collaborating. As a result, the company's recruitment implementation has not been able to achieve the specified target. This study aims to evaluate the implementation of the domestic apprenticeship program and identify the factors supporting and inhibiting the implementation of the domestic apprenticeship program in Lampung Province. The study was conducted with a qualitative descriptive approach using 3 indicators of the implementation of public private partnership (Public Private Partnership) consisting of policies, resources and communication (Kurniawan, Setianto et al., 2009). The results of this study indicate that the cooperation between the government and the private sector (public private partnership) in the program to increase labor competence and productivity (PKTKP) based on domestic apprenticeship in Lampung Province is quite effective. Viewed from the policy aspect, it can be said that it is effective because the purpose of holding this program is in accordance with the objectives of the government-private partnership which is beneficial in addition to providing services to the public but also providing benefits from companies that collaborate with the Lampung Province Manpower Office. In the aspect of resources, human resources in the implementation of this domestic apprenticeship program have not been maximized in achieving the desired target/results so that the resource aspect in this focus can be said to be less effective. In the communication that took place quite well, this was seen from the lobbying process to achieve the target of absorption of participants, although communication in the socialization process for recruiting companies had not yet reached the target.